Comparing the Same Task in ESL vs. EFL Learning Contexts: An Activity Theory Perspective. (11th July 2019) - Storch, Neomy; Sato, Masatoshi
Abstract : This classroom‐based study examined the role of context in task‐based interaction. Identical tasks were implemented in university‐level classes in two contexts: Australian ESL ( n = 27) and Chilean EFL ( n = 19). The learners engaged in discussion tasks, as part of the regular classroom activities. Data included audio‐recorded task‐based interactions, observations, and a survey. Data analysis was guided by activity theory, examining how learners approached the tasks, including deliberations about language (actions), the group dynamics, and their use of mediating tools (e.g., L1). Our findings revealed differences in the learners' actions in these two contexts, both expected (e.g., use of L1) and unexpected (e.g., the nature of assistance provided). Our study shows that in different contexts, the same tasks represent different learning activities. Abstract : 本稿は、学習環境がクラスルームにおけるタスク活動にどのような影響を及ぼすかを探るものである。オーストラリアの第二言語環境(ESL: n = 21)とチリの外国語環境(EFL: n = 19)において、大学生が同様のタスクに従事した。タスクは個人的意見交換を促進するもので、通常の授業の一環として使われた。データとして、録音されたタスク活動、授業観察、質問票が収集された。アクティビティー理論に基づき、学習者がどのようにタスクに従事したか、タスク中、どのように言語問題を解決したか、学習者間の社会関係、そして学習者が第一言語をどのように仲介として使用したか、を分析した。結果、学習者は、学習環境によって異なる活動に従事ることが明らかになった。本稿は、学習環境によって、同じタスクが同じ活動を必ずしも引き出さないことを論じる。